One Tree of a Thousand Hopes, Increasing Public Awareness of the Importance of Greening the Environment in Madana Village, Tanjung District, North Lombok Regency - Supriadin, Supriadin; Syahrir, Syahrir; Nurdin, Nurdin; Salabi, Muhammad (Abdi Masyarakat, 2024)
The objectives of the land revitalization service program activities through tree planting as an effort to increase public awareness of the importance of greening the environment in Madana Village, Tanjung District are to 1) increase and form awareness about conservation of land resources in the environment, 2) increase knowledge about the benefits of greening and protecting the environment, and 3) foster a sense of ownership and play a role in protecting the environment through planting and maintaining trees. The location of the activity is Madana Village, Tanjung District, North Lombok Regency on November 16 2024. Partners in the tree planting activity are youth, youth organizations and the Madana village community. Tree planting activities include planting planning, planting preparation, and the planting process. The service program activities as a whole can be said to be good and successful, based on measuring three components. The three components are conformity with community wishes, collaborative service with the community, and increasing community knowledge to protect the environment. It is hoped that with this activity there will be public awareness of the importance of greening the environment.